2020
DOI: 10.21203/rs.3.rs-118785/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elevated mature monocytes in bone marrow accompanied with a higher IPSS-R score predicts a poor prognosis in myelodysplastic syndromes

Abstract: Background: Myelodysplastic syndromes (MDS) is a group of heterogeneousmyeloid clonal diseases originating from hematopoietic stem cells. Clinically, elevated mature monocyte is often observed, but its clinical value still remains unclear.Methods: We retrospectively analyzed a cohort of 235 MDS patients to explore the prognostic value of the percentage of mature monocyte in bone marrow (PMMBM). All patients were divided into elevated PMMBM group and the normal group by 6% PMMBM as the cut-off value. Results: O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Patients exhibiting a CMML-like phenotype in the bone marrow also had a higher incidence of constitutional symptoms. Another study on bone marrow monocytosis [9] confirmed these findings and concluded that an increase in mature monocytes in the bone marrow is associated with inferior prognosis in patients with all types of MDS. Since our study included only patients without excess blasts, patient characteristics differed substantially between our cohort and the two aforementioned studies.…”
Section: Discussionmentioning
confidence: 78%
“…Patients exhibiting a CMML-like phenotype in the bone marrow also had a higher incidence of constitutional symptoms. Another study on bone marrow monocytosis [9] confirmed these findings and concluded that an increase in mature monocytes in the bone marrow is associated with inferior prognosis in patients with all types of MDS. Since our study included only patients without excess blasts, patient characteristics differed substantially between our cohort and the two aforementioned studies.…”
Section: Discussionmentioning
confidence: 78%